Philosophy of too much medicine conference report - Uusitalo, S; Howick, J (Wiley, 2018)
Medical scientists have expressed scepticism about whether philosophy is relevant to medicine. We challenged this in a conference on the topic of “too much medicine” (TMM) held in Oxford in April 2017. The topic of TMM provided an opportunity to bring the two disciplines together because of its history both in philosophy and in medicine. We found that the collaboration between the two disciplines was fruitful when two conditions were met. First, both disciplines had to avoid discipline‐specific jargon. Second, each discipline had to engage with the other. Specifically, medical scientists had to engage with some philosophical literature, and philosophers had to “get their hands dirty with data.” In this conference report, we provide an overview of our discussions and summarize the other papers in the series.